Simultaneous neurofibroma and schwannoma of the sciatic nerve. - Sintzoff, S A; Bank, W O; Gevenois, P A; Matos, C; Noterman, J; Flament-Durand, J; Struyven, J (American Journal of Neuroradiology, 1992)
The authors report a case of simultaneously occurring neurofibroma and schwannoma of the sciatic nerve and discuss the complementary aspects of MR and US. The schwannoma was well-defined and showed distal enhancement on sonographic evaluation, whereas the neurofibroma was ill-defined; both tumors were hypoechoic. T1- and T2-weighted MR images revealed similar signal characteristics of the two tumors, but intense enhancement following administration of gadolinium-DTPA distinguished the schwannoma from the neurofibroma.